2017
DOI: 10.1190/geo2016-0517.1
|View full text |Cite
|
Sign up to set email alerts
|

Seismic characterization of a carbonate reservoir in Tarim Basin

Abstract: Seismic characterization of carbonate reservoirs is a challenging task for geophysicists because of their special depositional environment and complex interior structures. We developed a case study of the seismic characterization of a karstified carbonate reservoir in the Tarim Basin, western China. The characterization procedure is sequential and includes fault and fracture detection, seismic facies classification, seismic impedance inversion, and lithofacies classification. We presented a dipsteered coherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…2). Small, anomalous bead-string reflections on seismic profiles of the Tarim Basin in northwestern China have been reported as evidence for seismic-scale caves, collapsed caves, or caves filled with sediment (Zeng and others, 2011a, b;Zhiqian and Tailiang, 2015;Rao and Wang, 2015;Xu and others, 2016;Liu and Wang, 2017;Zhu and others, 2017). Similar anomalous bead-string reflections have been identified on some of the seismic profiles from the west and east South Miami Heights 3D seismic surveys ( fig.…”
Section: Preliminary Seismic Characterization Of Karstmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Small, anomalous bead-string reflections on seismic profiles of the Tarim Basin in northwestern China have been reported as evidence for seismic-scale caves, collapsed caves, or caves filled with sediment (Zeng and others, 2011a, b;Zhiqian and Tailiang, 2015;Rao and Wang, 2015;Xu and others, 2016;Liu and Wang, 2017;Zhu and others, 2017). Similar anomalous bead-string reflections have been identified on some of the seismic profiles from the west and east South Miami Heights 3D seismic surveys ( fig.…”
Section: Preliminary Seismic Characterization Of Karstmentioning
confidence: 99%
“…Identification of caves on seismic profiles is important, because they could affect, at least locally, the groundwater flow system of the Floridan aquifer system in southeastern Florida. It has been suggested that caves are an important part of carbonate petroleum reservoir systems in the Tarim Basin (Zeng and others, 2011a, b;Zhiqian and Tailiang, 2015;Xu and others, 2016;Liu and Wang, 2017;Zhu and others, 2017). At the study area, in some cases, sagging seismic reflections overlying bead-string reflections suggest the caves have collapsed, and elsewhere, where no overlying seismic-reflection sag is present, it is possible the cave cavities or sediment-filled cave cavities are intact.…”
Section: Preliminary Seismic Characterization Of Karstmentioning
confidence: 99%
“…Li et al (2014) apply the residual signal matching tracing method to improve the lateral resolution of the top boundary of small-scale carbonate reservoirs, restore the shape of the SBRs, and help to identify small-scale reservoirs in limestone. Liu and Wang (2017) use seismic discontinuities, seismic facies classification, stochastic inversion, and lithofacies classification to detect faults and karst fractures in the carbonate reservoir. Lu et al (2018) apply the discrete frequency coherence attributes to detect the fractured-vuggy bodies in carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%
“…The Middle-Lower Ordovician carbonates have strong heterogeneity, and the karst reservoirs in the strata carry most of the oil and gas resources [3]. The target layer contains a large number of prolific oil and gas wells related to karst reservoirs [4]. After years of exploration and development, it has been recognized that abnormal seismic reflection is the main feature of Ordovician carbonate fractured-vuggy reservoir (FVR) [5].…”
Section: Introductionmentioning
confidence: 99%